An approach to Academic Discussion about Blended Learning (Docentes 2.0 Journal, 2021)
Blended Learning is a teaching modality that intertwines face-to-face and online classes components. The objective of this article was to present an outline of the scope, limits, challenges as well as gaps of Blended Learning, based on a review of the works published in the last six years, through interpretive analysis of the antecedents, definitions, benefits, challenges as well as their obstacles, the role of the teacher in blended environments, models, measurement of their effectiveness. This work is documentary research based on the qualitative interpretive approach. The findings show a gap in the consensus on a definition of this modality; a coincidence is found as a determining factor in training teachers to implement this model as the main challenge. In addition, a trend of measuring the effectiveness of the models based on the learner, as well as a predominant constructivist approach to implementation. To conclude, other urgent lines of research for Blended Learning are those related to its conceptual foundations, measurement of its effectiveness from a systemic perspective, detection of specific training needs in both didactic and technological skills, and competencies for teachers, specifically in hybrid contexts.
Keywords: Blended learning; higher education; information technology